Cyfres Yr Onnen - Wyn, Rhiannon (Y Lolfa, 2009)
Erin has recently moved into a smart old mansion which is featured on the TV programme 'Dy Dŷ' ('Your House'). The presenter, Robyn Rici, and Sara, Erin's mother, develop a relationship. But little do they know that Erin also has a friend. Madam Petra wants to make sure that Erin has fair play, in school and at home. The winner of the Tir.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books